Solve for a 7=-3-a

Math
7=-3-a
Rewrite the equation as -3-a=7.
-3-a=7
Move all terms not containing a to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
-a=7+3
Add 7 and 3.
-a=10
-a=10
Multiply each term in -a=10 by -1
Tap for more steps…
Multiply each term in -a=10 by -1.
(-a)⋅-1=10⋅-1
Multiply (-a)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1a=10⋅-1
Multiply a by 1.
a=10⋅-1
a=10⋅-1
Multiply 10 by -1.
a=-10
a=-10
Solve for a 7=-3-a

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top